Sorption and Desorption of Nutrients in Seawater By Zeolite - M. Prama Yufdy (Institut Teknologi Bandung, 2007)
Seawater contains large amounts of cations. Since this resource is abundant and cheap, it can be a laudable source of plant nutrients. The objective of this study was to investigate the extent to which zeolite could sorb and desorb nutrients in different concentrations of seawater. Results indicated that Zeolite sorbed Na and Mg. The highest percentage of Na and Mg sorbed was 76.19 and 36.69%, respectively obtained for 10% seawater. The desorption study indicated that the higher the seawater concentration used during the sorption, the higher the Na and Mg desorbed. Passing diluted seawater through zeolite leached out K and Ca to the extent that the effluent was concentrated with the cations. This by-product solution can be used as a source of plant nutrients. However, high concentration of such cations in the solution caused high pH and EC, which means that the solution has to be diluted to meet the requirements of plants.